A KEARIFAN LOKAL DALAM MENGATASI KONFLIK HORIZONTAL DI KABUPATEN KARO - rehulina sitepu; sugih ayu pratitis (Jurnal Perspektif Hukum, 2020)
The plurality of the Indonesian nation is one of the riches of the Indonesian nation which is rarely owned by other countries in the world. Each ethnic group in Indonesia has its own special customs and culture that become its identity. This does not mean that the existence of various ethnic groups with various special cultures must be eliminated in development. Development as a planned and desirable process must consider the existence of various ethnic groups and special cultures. Development should be carried out based on this reality which is harmonized with national interests. The research method used in the preparation of this study is a qualitative method. A good study always pays attention to the compatibility between the techniques used with the flow of general thought and theoretical ideas. The word qualitative method can be interpreted as a technique or procedure and theoretical idea. In the context of qualitative research, each other presupposes each other. For example, in the foregoing descriptions it will be explained that the purpose of using qualitative methods is to seek a deep understanding of a phenomenon, fact or reality. Facts, reality, concepts, symptoms and events can only be understood if the researcher tracks them in a manner that is not limited to just a view on the surface. Local wisdom (local wisdom) is understood as local (local) ideas that are wise, full of wisdom, good value, embedded and followed by members of the community. Where local local enthusiasm has a very important role for local communities in solving problems / conflicts that exist in social life.